Post-Traumatic Glioma: Report of a Case - Pokhrel, Bivek; Shrestha, Pranaya; Rajbhandari, Pravesh; Chandra, Avinash; Pant, Basant (Nepal Journal of Neuroscience, 2017)
Development of malignant glioma after trauma is a rare occurrence. Trauma and scarring have been known to be the predisposing factor for the development of meningiomas. Many people have discussed about the development of glioma post trauma but without proper evidence of documents prior to trauma with no evidence of tumor. We present you a case with evidence of not having tumor during trauma. Nepal Journal of Neuroscience, Vol. 14, No. 2,  2017 Page: 43-46